Bit-error rate simulation for wideband code-division multiple-access (WCDMA) systems over composite effects of partial-band noise interference and multi-tone interference - Lee, Brenda Jie Ying (2017)
Wireless communications are becoming increasingly popular, with wideband code-division multiple-access (WCDMA) being the designated air interface for Third-Generation (3G) mobile communication systems. However, the performance of WCDMA systems is limited by several factors, such as the presence of various forms of interference. Possible forms of interference include additive white Gaussian noise (AWGN), partial band noise interference (PBNI), single-tone jamming (STJ), multi-tone jamming (MTJ) and pulsed noise jamming. The aim of this project is to develop a simulation model within MATLAB, so as to obtain the bit-error rate (BER) performance of a WCDMA system in an AWGN channel under the composite effects of PBNI and MTJ. In addition, the BER performance of the system under Rayleigh fading conditions will be explored.